2016
DOI: 10.18632/genesandcancer.122
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CETP as a molecular target for estrogen positive breast cancer cell death by cholesterol depleting agents

Abstract: Cholesterol and its metabolites act as steroid hormone precursors, which promote estrogen receptor positive (ER+) breast cancer (BC) progression. Development of cholesterol targeting anticancer drugs has been hindered due to the lack of knowledge of viable molecular targets. Till now, Cholesteryl ester transfer protein (CETP) has been envisaged as a feasible molecular target in atherosclerosis, but for the first time, we show that CETP contributes to BC cell survival when challenged with cholesterol depleting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…On the other hand, at the 24‐hr time‐point, many genes were consistently upregulated in at least four cell lines. Table 1 displays the list of these genes, the information on family, molecular function ligands (lipid transport‐associated), subcellular localization, and cancer‐associated expression patterns of their encoded proteins are also provided (Carrara et al., 2018; Chen et al., 2020; Esau et al., 2016; Gordon et al., 2019; D. Jiang et al., 2020; Koochekpour et al., 2007; Swanton et al., 2007; Thorsen et al., 2011; Verma et al., 2020; Yang, He, et al., 2019; M. Zhang, Xiang, et al., 2020; Zheng et al., 2018). It was observed that STARD4, OSBPL9 LDLR, and SCARB1 genes were significantly upregulated in all the LPDS‐treated (24 hr) cell lines, whereas CERT1, OSBPL5, OSBPL1A, APOLD1, APOL5, CTEP, PSAP, CFHR4, APOO, and SLC27A6 were upregulated in at least four of the five cell lines (Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, at the 24‐hr time‐point, many genes were consistently upregulated in at least four cell lines. Table 1 displays the list of these genes, the information on family, molecular function ligands (lipid transport‐associated), subcellular localization, and cancer‐associated expression patterns of their encoded proteins are also provided (Carrara et al., 2018; Chen et al., 2020; Esau et al., 2016; Gordon et al., 2019; D. Jiang et al., 2020; Koochekpour et al., 2007; Swanton et al., 2007; Thorsen et al., 2011; Verma et al., 2020; Yang, He, et al., 2019; M. Zhang, Xiang, et al., 2020; Zheng et al., 2018). It was observed that STARD4, OSBPL9 LDLR, and SCARB1 genes were significantly upregulated in all the LPDS‐treated (24 hr) cell lines, whereas CERT1, OSBPL5, OSBPL1A, APOLD1, APOL5, CTEP, PSAP, CFHR4, APOO, and SLC27A6 were upregulated in at least four of the five cell lines (Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, at the 24-hr time-point, many genes were consistently upregulated in at least four cell lines. Table 1 displays the list of these genes, the information on family, molecular function ligands (lipid transport-associated), subcellular localization, and cancer-associated expression patterns of their encoded proteins are also provided (Carrara et al, 2018;Chen et al, 2020;Esau et al, 2016;Gordon et al, 2019;D. Jiang et al, 2020;Koochekpour et al, 2007;Swanton et al, 2007;Thorsen et al, 2011;Verma et al, 2020;Yang, He, et al, 2019;M.…”
mentioning
confidence: 99%
“…The stage-related expression of these genes suggests their potential role in the disease progression and utility as monitoring markers or therapeutic targets. The cholesteryl ester transfer protein (CETP) for example maintains cholesterol homeostasis and has been identified as a potential target for estrogen positive breast cancer 60 . Conversely, AHNAK can act as a tumour suppressor gene and mediates the negative regulation of cell growth 61 .…”
Section: Discussionmentioning
confidence: 99%
“…The stage-related expression of these genes suggests their potential role in the disease progression and utility as monitoring markers or therapeutic targets. The cholesteryl ester transfer protein (CETP) for example maintains cholesterol homeostasis and has been identi ed as a potential target for estrogen positive breast cancer (54). Conversely, AHNAK can act as a tumour suppressor gene and mediates the negative regulation of cell growth (55) While our work provides a signi cant amount of novel information regarding the behavior of cancerrelated molecules in esophagus and stomach tumors, it does not assess the level of gene expression based on the molecular classi cation of stomach and esophageal cancers (7).…”
Section: Discussionmentioning
confidence: 99%